Professionalism as proxy for business education: Considering Arts and Science majors pursuing business minors. Issue 2 (April 2017) - Way, Amy K; Marinelli, Samantha; Jaworski, Kasia; Diment, Ashley; Buterbaugh, Kaitlyn; Ventura, Vincent
With increased scrutiny over the value and promise of higher education, liberal arts degrees face criticism, in favor of professional degrees like business that position students for a linear career path to lucrative work. Research for this article is based on 20 interviews with college students majoring in Arts and Sciences, who completed a summer program to obtain a business minor. Our findings demonstrate that participants talk about the business minor as a key factor in 'selling themselves' to potential employers by (1) highlighting the discipline required to complete the program, (2) acting as a conversation starter with potential employees, and (3) emphasizing the broad applicability of a business minor. Implications demonstrate the power of professionalism to render specialized knowledge (like business knowledge) insignificant while offering an extension of Williams' ideal-worker norm to young people.